Dihydrotanshinone I enhanced BRAF mutant melanoma treatment efficacy by inhibiting the STAT3/SOX2 signaling pathway - Luo, Xing; Duan, Yi; He, Jinwei; Huang, CongGai; Liu, Jun; Liu, Yifan; Xu, Mengdei; Dai, Qiong; Yang, Zhihui (Frontiers in Oncology, 2025)
BackgroundThe Food and Drug Administration has approved the Serine/threonine-protein kinase B-raf (BRAF) inhibitor and Mitogen-activated extracellular signal-regulated kinase (MEK) inhibitor combo as the first-line treatment for individuals with metastatic melanoma, although the majority of these patients exhibit primary or secondary drug resistance in the clinic. Dihydrotanshinone I (DHT) is a lipophilic compound extracted from the root of Salvia miltiorrhiza that has been linked to multiple antitumor activities. In this study, we investigated the effect of dihydrotanshinone I on the MAPK pathway inhibitor resistance of BRAF mutant malignant melanoma.MethodAfter treating A375, A375R, and A2058 cells with DHT or a combination of DHT and BRAF/MEK inhibitors, WB and Real-Time RT-qPCR were used to confirm the activation of the MAPK and STAT3/SOX2 pathways. CCK-8 was used to assess cell viability, while flow cytometry was used to identify apoptosis. In addition, mice were inoculated with A375 cells to establish a model of tumour formation, and various drug groups and treatment models were utilized. The diameter and weight of tumours in each group were then measured, and IHC and HE staining were used to assess the expression of two pathways and cytotoxicity, respectively.ResultsThis study found that DHT directly interacts with STAT3 protein and it can stop the feedback activation of the STAT3/SOX2 pathway caused by the use of MAPK pathway inhibitors. In addition, the combination of DHT and BRAF/MEK inhibitors can inhibit the proliferation and growth of BRAF mutant melanoma cells and primary and secondary drug-resistant cells. Finally, we proved that the combined therapy of DHT and BRAF/MEK inhibitors is reliable and effective at animal and cell levels.ConclusionIn BRAF mutant melanoma cells, DHT suppresses the STAT3/SOX2 signaling pathway. Combining DHT, BRAF inhibitors, and MEK inhibitors can help treat treatment-resistant BRAF mutant melanoma cells. Experimental results both in vitro and in vivo have shown that the combination of DHT and an inhibitor of the MAPK pathway is safer and more successful than using an inhibitor of the MAPK pathway alone when treating BRAF mutant melanoma.